Aspect ratio effects in Rayleigh–Bénard convection of Herschel–Bulkley fluids. Issue 5 (3rd July 2017) - Aghighi, Mohammad Saeid; Ammar, Amine
Abstract : Purpose: The purpose of this paper is to analyze two-dimensional steady-state Rayleigh–Bénard convection within rectangular enclosures in different aspect ratios filled with yield stress fluids obeying the Herschel–Bulkley model. Design/methodology/approach: In this study, a numerical method based on the finite element has been developed for analyzing two-dimensional natural convection of a Herschel–Bulkley fluid. The effects of Bingham number Bn and power law index n on heat and momentum transport have been investigated for a nominal Rayleigh number range (5 × 10 3 < Ra < 10 5 ), three different aspect ratios (ratio of enclosure length:height AR = 1, 2, 3) and a single representative value of nominal Prandtl number ( Pr = 10). Findings: Results show that the mean Nusselt number Nu ¯ increases with increasing Rayleigh number due to strengthening of convective transport. However, with the same nominal value of Ra, the values of Nu ¯ for shear thinning fluids n < 1 are greater than shear thickening fluids n > 1. The values of Nu ¯ decrease with Bingham number and for large values of Bn, Nu ¯ rapidly approaches unity, which indicates that heat transfer takes place principally by thermal conduction. The effects of aspect ratios have also been investigated and results show that Nu ¯ increases with increasing AR due to stronger convection effects. Originality/value: This paper presents a numerical study of Rayleigh–Bérnard flows involving Herschel–Bulkley fluids for a wide range of Rayleigh numbers, Bingham numbers and power law index based on finite element method. The effects of aspect ratio on flow and heat transfer of Herschel–Bulkley fluids are also studied.